Digitally proportional gain varying method for DC-DC converter - Furukawa, Yudai; Shirakawa, Takuya; Kurokawa, Fujio; Colak, Ilhami (Intelec, 2015)
The purpose of this paper is to propose a digitally proportional gain varying method for dc-dc converter. In the proposed method, the proportional gain is set to a small value in the steady state and is changed to a large value over stability limit for only a short time in the transient state. Using the proposed method, the transient response can be improved while the dc-dc converter system is kept in stable. Compared with the conventional PID control, the undershoot and the convergence time are improved by 69% and 75%, respectively. Furthermore, the capacitance of output smoothing capacitor must be set to a large value to maintain the stability of system when the control gain is set to a very large value. However, that can be reduced because the very large gain is set for only a short time to improve the transient response in the proposed method. Therefore, the miniaturization of main circuit can be expected.